Audit of Antibiotic Prescription in Suspected Neonatal Sepsis at an Indian Tertiary Care Hospital - Geetha S; Deepa Patil; Raghu Prasada M S; Sathisha Aithal (Universitas Padjadjaran, Indonesia, 2022)
Neonatal sepsis is one of the most typical causes of neonatal morbidity and mortality in the developing world. Rational use of antibacterial is a priority to prevent the emergence of resistance and to reduce the burden of treatment failure. This study was a prospective, cross-sectional study that collected data from 148 records of clinically suspected neonatal sepsis in a tertiary care hospital between January to December 2017. The isolated organisms, prescribing patterns, approval status, and list of antibacterial in WHO Essential Medicines List/NLEM were analyzed and presented as percentages, mean and standard deviations using appropriate tables and graphs. Of the 430 antibacterials examined, single-drug formulations were most commonly prescribed [400(93.02%)]; 298(69.30%) and 427(99.30%) were approved by DCGI and USFDA, respectively; 275(63.95%) antibacterials were included in both WHO and NLEM. The most common isolated organisms were gram-negative (64.1%). The most common class of antibacterial prescribed was beta-lactams (ATC class: J01D and J01C) [251(58.37%)] followed by aminoglycosides (ATC class: J01G) [124(28.84%)] irrespective of culture and sensitivity and their generic names prescribed almost 50% (216) of drugs. Regarding outcome, 87.16% of cases recovered well. In conclusion, the rationality of antibacterial drug usage in suspected cases of neonatal sepsis was followed the majority of times, leading to better patient care and outcome.